Application of Health Belief Model (HBM) With Sexual Behavior in Bandar Lor Mojoroto District Kediri 2022 - Ongki Orison Reonutu; Muhammad Ali Sodik (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2024)
Health belief model is a model used to describe an individual's belief in healthy living behavior, so that the individual will carry out health behavior in the form of preventive behavior. This health belief model is often used to predict preventive health behavior. The health belief model is used to predict various health-related behaviors. The main concept of the Health belief model is healthy behavior determined by individuals in Bandar Lor Village, Mojoroto District, Kediri City.This type of research is analytical observational with a cross sectional approach with a sample size of 54 respondents, taken using the Porposive Sampling technique. The data analysis used was univariate, bivariate, univariate analysis and the Chi Square test. The results of this research show that the statistical test results of Perceived Susceptibility (p=0.306), Perceived Severity (p=0.503), Perceived Benefit of Action (p=0.301), Cues to Action (p=0.209) have no relationship with sexual behavior. Meanwhile, Self Efficacy (p=0.003) has a relationship with sexual behavior. Based on the research results, it can be concluded that the perception related to sexual behavior is Self Efficacy. So it is hoped that teenagers can learn and increase their insight into the impact of sexual behavior so that they can avoid negative sexual behavior.